Production of kale seedlings on substrates containing proportions of organic compost (Research, Society and Development, 2021)
One of the difficulties in the kale seedlings production in containers is to ensure the production of aboveground biomass with a limited portion of roots, restricted to a small volume of substrate. Thus, we investigated whether substrates with organic compost added to it associated with kale cultivars interfere in the quality of seedlings produced in a greenhouse. Here, we studied two kale cultivars and five substrates. The experiment was designed in randomized blocks, with treatments arranged in a bifactorial scheme (2 x 5), with three replications. We carried out the physical and chemical characterization of the substrates and evaluated attributes of the aerial part and root system of the kale seedlings. The results showed that the substrate with the highest water retention was the one without the addition of organic compost. The greater the proportion of organic compound added to the substrate, the higher the nitrogen, phosphorus and organic carbon values. Seedlings produced in the substrate with greater water retention capacity had better performance in relation to the morphology of the aerial part and the morphology of the root system. We conclude that seedlings of kale cultivars associated with substrates with higher water retention have better quality. Seedlings of the ‘Gaudina’ cultivar stand out for their better phytometric morphology, while seedlings of the ‘Manteiga’ cultivar have higher quality of root biomass.